Performance Analysis of Baseflow Separation Methods: The Case of Rift Valley Lakes Basin, Ethiopia - Dawit Midagsa Abdi (MO.RI Publishing, 2022)
Adopting the appropriate method to separate baseflow from stream flow is desirable for future low flow prediction, planning, management of water resources, and nourishing the environment as well. Thus, comparing the baseflow separation method is inevitable unfortunately not studied within the basin. Therefore, in this study, seven recursive digital filters (RDF) and two digital graphical (DGM) methods were compared in rift valley lakes basins. All the methods were calibrated manually with the help of BFI 3.0 tool; the performance of each method was checked by R2 and RMSE, taking the separation with maximum R2 and minimum RMSE were taken as appropriate separation method and (Baseflow Index) BFI was calculated by using the baseflow from the suitable method for each catchment. The outcomes of baseflow separation indicate that two methods (exponentially weighted moving average (EWMA) and Lynie-Holick) performed better than the other seven methods; unlikely, local minimum and one parameter methods perform less by both R2 and RMSE. Therefore, these comparisons could possibly elucidate the baseflow prediction in the majority of catchments. Subsequently, existing and forthcoming water resource improvement attempts may employ this estimation approach for low flow forecasting, baseflow trend analysis, as well as planning and designing water resources projects.